Neglect of Temperature and pH Impact Leads to Underestimation of Seasonal Ecological Risk of Ammonia in Chinese Surface Freshwaters - Zhen-Guang Yan; Jun-Tao Fan; Xin Zheng; Shu-Ping Wang; Xiao-Shan Guo; Tian-Xu Zhang; Su-Wen Yang; Yi-Zhang Zhang (Journal of Chemistry)
Ammonia nitrogen (AN) is evaluated with fixed water quality standards (WQSs) in aquatic environment management in China. Since the toxicity of AN can be influenced by water parameters, the current evaluation is not rigorous and may result in problematic conclusions. The present study collected the ecotoxicity and exposure data of AN in Chinese surface freshwaters in 2017. The species sensitivity distribution of AN was established, and the ecological risk posed by AN in Chinese surface waters was assessed with Chinese AN water quality criteria. The results showed that mollusk species are the most sensitive taxa to AN. Ecological risk assessments on AN suggested that, in summer and autumn, when the water temperature and pH are high, the risk of AN may occur at some sites with good water quality (Class II or III). This poses a threat to aquatic organisms at these sites, especially highly sensitive freshwater shellfish. It suggested that neglect of water parameters impact may lead to underestimation of ecological risk of AN in Chinese basins.